Human biography – the arena of democratic negotiations - Teusz, Grażyna (Kultura-Społeczeństwo-Edukacja, 2020)
The subject-matter of this paper is an attempt to outline the type of relationship that exists between democracy and the autonomous and responsible individual as a necessary pre-condition for a real and genuine community. The author’s reflections are focused around the idea that onlya conscious, inner-directed and mature individual can guarantee a solid foundation for the rules and practice of democracy and that human biography is the actual arena of democratic negotiations constantly being undertaken.